Analisis Rencana Anggaran Biaya Pembangunan Pos Jaga Militer di Perbatasan Indonesia-Papua Nugini - Suprayogi, Suprayogi; Sitorus, Andreas Robert Panogu; Sihombing, Gian Felix; Daffarel, Rakyan Choiruna; Safaraz, Mohammad Bhampy Nugraha; Iswanto, Dian Sasmita; Pelu, Muhammad Rijali Sukur; Angelia, Ervina Wiedyasta; Laksmi, Anasya Arsita (Universitas Ibn Khaldun, 2025)
This research aims to determine the costs required to build a guard post building in the border area of Papua, Indonesia and Papua New Guinea. It is hoped that this research will contribute to improving the national defense, especially regarding the construction of guard posts in national border areas. This research discusses the construction of the guard post by describing the volume of work and the planned cost budget, and the data collection methods used are primary and secondary data. In this research, guard post drawings were planned according to the standards of the Indonesian Army and supporting data in the form of Unit Prices for Goods and Services (SHBJ) in the Papua region, as well as the Ministry of PUPR's Unit Price Analysis Guidelines. Apart from that, the type of work along with the volume of work is arranged followed by an analysis of the unit price of each job. Then the Cost Budget Plan (RAB) is calculated to get the total price for each job. Thus, the total cost required to build a guard post building on the Papua border is IDR 119,441,000.00. In the future, it is hoped that this research can become a reference for building guard posts around the Papua border area.